TEKNIK PEMERIKSAAN KEDOKTERAN NUKLIR SIDIK TIROID DI INSTALASI RADIOLOGI RSUP DR. KARIADI SEMARANG - Nanik Sudaryatmi; Siti Masrochah; Rasyid Rasyid (Jurnal Imejing Diagnostik (JImeD), 2020)
Background: Examination of thyroid scintigraphy or thyroid gland scintigraphy is a nuclear medicine examination using radioactive substances or radiopharmaceuticals that are inserted into the body through intravenous injections which aim to obtain functional morphological imaging of the thyroid and to assess the ability of the thyroid gland to capture radioactive substances or radiopharma-ceuticals.Methods: This imaging prosedure using Tc-99m (Technisium-99m) radiopharmaceuticals as much as 2-5 mCi. To get maximum results, patients are asked to stop taking drugs that can interfere with iodine accumulation in the thyroid gland.Results: Imaging was carried out 10-15 minutes after injection of the radiopharmaceutical. Marked with the thyroid cartigalo, jugulum and surgical sutures. The scanning process lasts for 5-10 minutes.Conclusions: The imaging results of hot nodules are generally identical to autonomic thyroid nodules, about 10-30% of cold nodules are found in the thyroid malignancy process while the rest are thyroid cysts.